Peripheral CD4+ T cells correlate with response and survival in patients with advanced non-small cell lung cancer receiving chemo-immunotherapy - Yang, Xin; Li, Qiao; Zeng, Tianyang (Frontiers in Immunology, 2024)
Background The aim of the present study was to explore the potential of peripheral immune cells in predicting the response and prognosis of patients with advanced non-small cell lung cancer (NSCLC) receiving anti-PD-1 immunotherapy and platinum-based chemotherapy. Participants and Methods We utilized flow cytometry to examine the levels and dynamics of blood immune cells in 79 advanced NSCLC patients treated with the chemoimmunotherapy between December 2019 and January 2022. The pre- and post-treatment blood samples were collected within 3 days prior to the initiation of the first and third cycle of combination treatment, respectively. Progression-free survival (PFS) and overall survival (OS) analyses were conducted using Kaplan-Meier method and Cox regression models. Results The pre-treatment CD4+/Total T cells ratio was significantly higher in responders than non-responders (P < 0.05). The levels of pre-treatment total lymphocytes (P = 0.012), total B lymphocytes (P = 0.025), and NK cells (P = 0.022), and post-treatment NK cells (P = 0.011) and NKT cells (P = 0.035) were significantly associated with OS. Post-treatment CD8+/Total T cells ratio was positively correlated with OS (P = 0.038). In multivariate analysis, post-treatment NK cells and post-treatment CD4+CD8+/Total T cells ratio were negatively associated with OS (hazard ratio [HR] = 10.30, P = 0.038) and PFS (HR = 1.95, P = 0.022), respectively. Notably, significantly positive correlations were observed between CD4+/Total T cells ratio and prognosis both before and after treatment (P < 0.05). Conclusion To summarize, our finding reveals that high CD4+/total T cells ratio was associated with favorable response and prognosis, highlighting its potential as a predictive biomarker to guide the selection of likely responders to platinum and anti-PD-1 combination therapy.